2018
DOI: 10.1002/jso.25039
|View full text |Cite
|
Sign up to set email alerts
|

Relapse in dermatofibrosarcoma protuberans: A histological and molecular analysis

Abstract: Surgical margins smaller than than 2 cm are related to higher recurrences in dermatofibrosarcomas. In this analysis a 2 cm margin was acceptable for treatment. Between all the immunohistochemical markers analyzed, only FasL was associated with a higher recurrence rate in patients with margins smaller than 3 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 41 publications
(64 reference statements)
0
7
0
2
Order By: Relevance
“…DFSP is a slowly growing mesenchymal neoplasm, characterized by high morbidity due to its local invasion and high recurrence rate after surgical excision [12,13]. The peak age at onset is between 20 and 50 years, and incidence among women is 1.14 times higher than in men [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFSP is a slowly growing mesenchymal neoplasm, characterized by high morbidity due to its local invasion and high recurrence rate after surgical excision [12,13]. The peak age at onset is between 20 and 50 years, and incidence among women is 1.14 times higher than in men [14].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical excision remains the mainstay treatment for DFSP. Because of its infiltrating growth pattern, a wide excision with margins of at least 3 cm of clinically uninvolved skin is strongly advised for the treatment of DFSP [13,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In case of regular histopathological processing (conventional histological margin control), wider surgical margins of at least 2 cm are recommended. In a retrospective analysis of 61 DFSP patients, surgical margins of less than 2 cm were associated with a significantly increased risk of recurrence . A systematic review of 23 nonrandomized trials comparing recurrence rates in patients treated with micrographic surgery versus wide local excision (combined with conventional histological examination of margins) revealed the former to be superior (recurrence rate 1.11 % versus 6.32 %) [9].…”
Section: Treatmentmentioning
confidence: 99%
“…Patients without this fusion had a high risk of recurrence in our series, which might be of limited significance due to the very small cohort ( n = 2). Molina et al 39 reported a similar result in adult DFSP, though. As the fusion turns on the PDGF signaling, the PDGF inhibitor imatinib was recommended as an alternative treatment for unresectable, metastatic or recurrent DFSP.…”
Section: Discussionmentioning
confidence: 75%